Cognitive Load Assessment in Multitasking: An fNIRS Study of Prefrontal Cortex Activation for Ergonomic Insight - Ridwan Aji Budi Prasetyo; Herdias Hayyal Falahi; Rais Reskiawan A. Kadir; Hardianto Iridiastadi (The Industrial Engineering Department of Engineering Faculty at Universitas Andalas, 2025)
Although traditional neuroimaging techniques like fMRI and EEG have yielded insightful results, their rigid movement limitations restrict their practical use. Functional near-infrared spectroscopy (fNIRS) offers a practical alternative by allowing researchers to measure cortical activity during more natural task performance, particularly in the prefrontal cortex (PFC)—a key region for attention and executive control. This study uses fNIRS to investigate how multitasking demands affect PFC activation. An eight-channel fNIRS system recorded the brain activity of thirty participants as they completed tasks from the Multi-Attribute Task Battery (MATB). Oxygenated hemoglobin (HbO) signals were the main focus of data preprocessing, and AtlasViewer was used to visualize cortical projections. The superior and middle frontal gyri, which are linked to the dorsolateral prefrontal cortex (dlPFC), showed a significant increase in HbO responses when multitasking. On the other hand, lower activation levels were produced under less demanding circumstances. These results are consistent with resource-based models of attention, which postulate that the brain allocates more cognitive resources, especially in the right PFC, as task complexity increases. Beyond theoretical ramifications, this study shows that fNIRS can be used to detect cognitive load in real time. In high-stakes settings like aviation, healthcare, and mission-critical operations, this capability has potential uses in adaptive systems intended to monitor and reduce mental overload. This study emphasizes fNIRS as a useful tool for comprehending and managing multitasking in today's dynamic work contexts by bridging laboratory research and real-world settings.